1996
DOI: 10.1088/0954-3899/22/10/008
|View full text |Cite
|
Sign up to set email alerts
|

Strong absorption formalism applied to the direct transfer reaction leading to continuum states

Abstract: Continuum energy spectra of the transfer reaction at 50 MeV are calculated and compared with experiment. A numerical treatment of the finite range distorted-wave Born approximation (DWBA) is used, with a strong absorption parameterisation of the radial matrix elements. The parameters of the S-matrix in the entrance and exit channels are obtained from elastic scattering data using a strong absorption parameterisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Using reasonable value of r α =1.45 fm [23][24] and the strong absorption radius for α + 58 Ni obtained from the present analysis (6.44 fm), yield a value of r 0 =1.29 fm. From a similar analysis of this scattering process but at 43MeV laboratory energy, a value of 1.36 fm is rather obtained from the fitting which becomes 1.5fm when the above value of r α is used instead [11]. Table 1.…”
Section: Elastic Scattering Of α + 58 Nimentioning
confidence: 99%
See 2 more Smart Citations
“…Using reasonable value of r α =1.45 fm [23][24] and the strong absorption radius for α + 58 Ni obtained from the present analysis (6.44 fm), yield a value of r 0 =1.29 fm. From a similar analysis of this scattering process but at 43MeV laboratory energy, a value of 1.36 fm is rather obtained from the fitting which becomes 1.5fm when the above value of r α is used instead [11]. Table 1.…”
Section: Elastic Scattering Of α + 58 Nimentioning
confidence: 99%
“…Such effects may be described by a function defined by the Fourier transform of an absorptive shape function. In the presence of strong absorption, several theoretical investigations were based on numerical and analytical treatments of the partial wave expansion model for elastic scattering [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Most of these investigations showed clearly how sensitive the scattering data for strongly absorbed particles are to the detailed form of the scattering matrix around the grazing angular momentum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The S-matrix, which represents the effect of the scattering potential on the incident wave, may be determined fitting its angular momentum components to the measured elastic angular distribution. It has been found that the parameterised S-matrix is a source of important information which is needed in calculations of transfer reactions based on the strong absorption model [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to study the reactions of 7 Li on 56 Fe have been made [1,2]. Excitation functions and differential recoil range distributions for different radioactive products of the 7 Li on 56 Fe reaction together with inclusive proton, deuteron, triton and alpha spectra, have been measured up to E( 7 Li) = 89 MeV [1].…”
Section: Introductionmentioning
confidence: 99%